A multiple‐standards framework to address externalities resulting from meat production. Issue 2 (15th February 2021) - Vissers, Luuk S. M.; Jongeneel, Roel A.; Saatkamp, Helmut W.; Oude Lansink, Alfons G. J. M.
Abstract: This article develops a framework for assessing the implementation of standards in a context of multiple negative externalities resulting from meat production. The framework is applied to the introduction of the New Dutch Retail Standard in the Dutch broiler market, a standard on animal welfare initiated by the private sector with national coverage. The results show that this standard did not lower producer, retailer, and consumer welfare; rather, social welfare increased by approximately 300 million euros. The framework provides a sound scientific basis for an ex ante analysis on the market potential of multiple standards. JEL CLASSIFICATION: D62; Q13; Q18